2017
DOI: 10.1111/ped.13349
|View full text |Cite
|
Sign up to set email alerts
|

Role of surgery in delayed local treatment for INSS 4 neuroblastoma

Abstract: Gross total resection/subtotal resection with local irradiation may be a safe and effective delayed local treatment for INSS 4 NB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Metastatic disease is found in about half the cases at the time of diagnosis, with most frequent sites of metastatic disease being bone and bone marrow, involving osseous structures from the skull and spine to appendicular skeleton, followed by liver, and skin (3). (3,6). Previous studies showed that 123 I-single photon emission computed tomography combined with CT (SPECT/CT) imaging provides better assessment of metastatic disease as compared to planar 123 I-MIBG imaging due to improved anatomical localization and improved lesion contrast in SPECT/CT versus planar imaging (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic disease is found in about half the cases at the time of diagnosis, with most frequent sites of metastatic disease being bone and bone marrow, involving osseous structures from the skull and spine to appendicular skeleton, followed by liver, and skin (3). (3,6). Previous studies showed that 123 I-single photon emission computed tomography combined with CT (SPECT/CT) imaging provides better assessment of metastatic disease as compared to planar 123 I-MIBG imaging due to improved anatomical localization and improved lesion contrast in SPECT/CT versus planar imaging (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…INSS is one of the most commonly used NB staging systems in clinical practice. Patients with NB in the INSS stages III-IV usually suffer from tumor infiltration or lymph node and distant metastases, and simple surgical treatment is considered insufficient for complete removal of the lesion, resulting in poor prognosis [ 12 , 13 ]. Prior research has found that preoperative adjuvant chemotherapy can effectively facilitate surgical resection and prolong the 5-year survival of the patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Hence, the treatment strategy may have advantages in terms of surgical invasiveness and the rates of postoperative complications and recurrence. [ 29 ] Nevertheless, other study showed no substantial survival benefit in patients with high-risk NB undergoing gross total tumor resection. [ 30 ] Multidisciplinary intensive treatment was essential, especially for patients who received STR.…”
Section: T Reatmentmentioning
confidence: 99%